Enhancing Self-Regulated Learning in a Borderline Student: Case-Based Evidence from a Self-Management Approach - Ilham, Muhammad; Ropawandi, Doni; Karnangsyah, Emi; Halimastussa’diah, Siti (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
Slow learners are often overlooked in educational systems, despite their increased vulnerability to academic underperformance, low motivation, and poor self-regulation. Homework performance, as an essential component of independent learning, is particularly problematic among this population due to cognitive limitations and unsupportive home environments. This study aimed to explore the psychological profile and academic challenges of an Indonesian adolescent with slow learner characteristics and to evaluate the effectiveness of a structured self-management intervention in improving his homework behavior. A single-case qualitative design was employed. Data were collected through psychological assessments (short-form intelligence test, projective drawings), behavioral observations, and interviews with the student, parent, and teacher. The intervention included five sessions focusing on self-monitoring, goal-setting, and parental psychoeducation over a three-week period. Pre- and post-intervention data were compared to evaluate changes in task behavior and self-efficacy. The student initially showed low homework completion (30–40%), avoidance behavior, and emotional frustration. Post-intervention results indicated significant improvement in task initiation, attention span, and completion rate (80–90%). The student demonstrated greater confidence and independence, while the parent and teacher reported increased engagement and self-regulation. The gains were sustained across subjects and home settings.